EVALUASI NILAI WATERFRONT PADA RUANG TEPI SUNGAl DI TENGAH KOTA KASUS KOTA SEMARANG - VG VG Sri Rejeki (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
In the Central Java people's perception, the river is blackside and outcast area. Some disasters on the riverbank have expressed the velopment inconsidersation of the water potention. research is to find out the concept of the waterfront application on the riverbank development. Using correlation between the human behaviour and the the environment (Rapoport, 1977), the research is aimed to get support theories and the classifications aspects of waterfront. This research has 5 cases. Three (3) cases explain about Semarang as the coastal city, and two (2) cases explain about Semarang as the historical city that has river water transportauon. The research found that the waterfront in Semarang has 3 clasifications, First, by the fishermen in the fishermen settlement, the clasification of waterfront was not only the building on the river but also as the people activity related to the river. Second, by the non fisherman live in the riverbank settlement, the classification of waterfront was only related to the view of the river not its activity. Those people have used only the riverbank space. Third, by the inhabitans of the city in the kampung kola, the classification was not related to waterfront orientation. The riveronly seen as edges the district an administrative border. Finnaly, the public's argument that if the river is cleaner, the application of the waterfront concept can be fuller than before. The research recommend that it was very important to threat the river carefully, since it can give benefit for some aspec in the future.